Atmospheric plasma treatments of cashmere: The role of nanoscale sizing in the spray coating processing - Barni, R.; Roman, H. E.; Citterio, A.; Leonardi, G.; Riccardi, C. (Frontiers in Materials, 2022)
We discuss the effects of air atmospheric plasma interaction with the surface of a textile. We 4 studied how plasma can promote changes in its texture and roughness at nano- and micro-meter 5 scales, having an impact on the improvement of such macroscopic properties as hydro/oleo6 repellency and pilling, without altering the hand assessment quality of the textile. These results are 7 obtained by analyzing images taken using electron microscopy. We studied both the fluctuations of 8 the image intensity at the fibre surfaces and their Fourier transforms at the sub-micrometer scales. 9 As a case study, we have analyzed the modifications of a cashmere fabric and the improvement 10 of finishing using resin spray coating. We observe a better efficiency when resin is applied to a 11 plasma treated sample. This result has been traced to the modifications that plasma induces on 12 the surface at the nanoscale. (We studied how plasma can promote changes in the texture and 13 the roughness at the nanometer scales. As a case study we have analyzed the modifications of 14 a cashmere fabric and the improvement of finishing using resin spray coating, whose efficiency 15 we observe to be boosted by previous plasma processing.) This opens up wide perspectives to 16 use plasma technology for the whole textile industrial sector.